KEMAMPUANPEMAHAMANMATEMATISBANGUNDATARSEGIEMPATSISIWASMP BERDASARKANLEVELKOGNITIFDIMASAPANDEMICOVID-19 - Rini Sri Bintang; Sutarjo Sutarjo; Ramlah Ramlah (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2021)
This research aims describe the ability to understand mathematical concepts based on their cognitive level. The research method is descriptive qualitative. The subjects were selected by 3 students based on their cognitive level using purposive sampling technique, obtained one student in the high, medium and low categories. Data collection through tests, interviews, and documentation analyzed through stages of data reduction, presenting data, and drawing conclusions. Based on results of data analysis, it found that students' ability to understand mathematical quadrilateral is cognitive level high and moderate are able to solve problems on indicators providing examples and not examples of a concept. And students a high cognitive level are able to solve problems on indicators restating a concept. Meanwhile, students a low cognitive level were unable to solve any of questions. So students at high, medium and low cognitive levels are unable to solve problems on the indicators of classifying objects according to certain properties according to the concept, and applying the concept of algorithms in problem solving. So can concluded that ability to understand the mathematical concepts of the material of sagiempat flat is low.